2013
DOI: 10.1002/jbm.b.32887
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trade‐offs in cross‐linked ultrahigh‐molecular‐weight polyethylene used in total joint arthroplasty

Abstract: Highly cross-linked formulations of ultrahigh-molecular-weight polyethylene (XLPE) offer exceptional wear resistance for total joint arthroplasty but are offset with a reduction in postyield and fatigue fracture properties in comparison to conventional ultrahigh-molecular-weight polyethylene (UHMWPE). Oxidation resistance is also an important property for the longevity of total joint replacements (TJRs) as formulations of UHMWPE or XLPE utilizing radiation methods are susceptible to free radical generation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…When used in primary THA, XLPE has a lower rate of revision for any reason than conventional PE ( AOANJRR 2013 ). Different companies continue to use different manufacturing methods for each XLPE product, aiming to balance resistance to wear, oxidation, and fatigue fracture ( Pruitt et al 2013 ). Ideally, as with all new prosthetic components, new XLPEs should be rigorously tested in clinical trials before being released for general use because of potential variation in manufacturing methods, which may lead to possible failure ( Rohrl et al 2005 , Malchau et al 2011 ).…”
Section: The Introduction Of Xlpementioning
confidence: 99%
“…When used in primary THA, XLPE has a lower rate of revision for any reason than conventional PE ( AOANJRR 2013 ). Different companies continue to use different manufacturing methods for each XLPE product, aiming to balance resistance to wear, oxidation, and fatigue fracture ( Pruitt et al 2013 ). Ideally, as with all new prosthetic components, new XLPEs should be rigorously tested in clinical trials before being released for general use because of potential variation in manufacturing methods, which may lead to possible failure ( Rohrl et al 2005 , Malchau et al 2011 ).…”
Section: The Introduction Of Xlpementioning
confidence: 99%
“…Developments during the last decades have presented significant changes in manufacturing and sterilization methods, as well as material technologies, enhancing the mechanical properties, oxidative stability, and wear of UHMWPE [13,14]. However, such an apparent trade-off between each of these factors with increasing cross-linkage is associated with a decrease in fatigue resistance [13,14]. There have been several investigations of substitute materials for UHMWPE, including poly-ether-ether-ketone (PEEK) and carbon-fiber-reinforced PEEK (CFR-PEEK).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the wear rate of PE increases due to the presence of scratches on the counterface and the presence of third‐body particles such as bone chips, bone cement, metal beads, broken wires, particles of bone, and other wear debris . It has been found that crosslinking with irradiation has improved the wear resistance of conventional UHMWPE, with a concomitant reduction in mechanical properties such as ultimate tensile strength, ductility, fracture toughness, and fatigue crack propagation resistance . Therefore, a number of researchers have raised concerns regarding the long‐term durability of XLPE .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that crosslinking with irradiation has improved the wear resistance of conventional UHMWPE, with a concomitant reduction in mechanical properties such as ultimate tensile strength, ductility, fracture toughness, and fatigue crack propagation resistance . Therefore, a number of researchers have raised concerns regarding the long‐term durability of XLPE . In vitro and in vivo studies of hip arthroplasty have indicated that crosslinking can reduce PE wear by up to 80%–90% .…”
Section: Introductionmentioning
confidence: 99%